Rituximab prescription patterns and efficacy in the induction treatment of ANCA-Associated Vasculitis in a Belgian multicenter cohort. Issue 3 (3rd May 2020) - Chasseur, P.; Blockmans, D.; von Frenckell, C.; Nicolas, J-B.; Regniers, C.; Vandergheynst, F.
ABSTRACT: Introduction : The RAVE trial has revolutionized induction treatment of anti-neutrophil cytoplasmic antibodies (ANCA)-Associated Vasculitis (AAV)by demonstrating the non-inferiority of rituximab (RTX) compared with cyclophosphamide. Objectives : We studied AAV patients' characteristics, RTX prescription practices and efficacy in AAV induction treatment in four Belgian university hospitals. The patient population, selected according to the Belgian reimbursement criteria, was relatively homogeneous and comparable to the one of RAVE trial. Methods : 57 patients, receiving RTX as AAV induction therapyfrom May 2014 to June 2017 were enrolled in an observational retrospective multicenter trial involving four Belgian university hospitals. We focused on the type of AAV, ANCA specificity, prescriber's specialty, used reimbursement criteria, organ involvements, severity of the flares and finally RTX efficacy in AAV induction treatment by considering the RAVE primary (complete remission without prednisone) and secondary (complete remission with prednisone <10 mg) outcomes at 6, 12, 18 and 24 months. Results : 66.7% of the patients reached complete remission with prednisone <10 mg at 6 months, 55.3% at 12 months, 40% at 18 months and 25% at 24 months. The rates of complete remission without steroids were very low at 6, 12, 18 and 24 months. The rates of relapses were high between 18 and 24 months. Conclusions : Our results confirm those of RAVE regarding complete remission rates with prednisone <10 mg/day, in a 'real-life' cohort of patients selected according to data of RAVE trial. The high prevalence of relapses – especially after 18 months – underlines the need to optimize maintenance treatment after an induction treatment with RTX.